One Year on: The Impact of COVID-19 on the Lives of Freelance Orchestral Musicians in the United Kingdom - Cohen, Susanna; Ginsborg, Jane (Frontiers in Psychology, 2022)
Before the drastic disruption caused by the sudden emergence of the COVID-19 pandemic, 85% of the UK’s 14,000 orchestral musicians were self-employed freelance workers, engaged in busy, varied portfolio careers comprising a combination of orchestral, West End theatre, chamber music and commercial recording work. Between May and June 2020 we carried out a first study examining the impact of the pandemic on the lives of 24 self-employed orchestral musicians, all established freelancers. Twelve were mid-career and 12 were late-career (described in that study as “seasoned”). They all reported having lost their much-loved performing careers, missing music making and colleagues, and being anxious about the future of the music profession. However, there were some differences between the two groups: the late-career participants demonstrated greater financial and emotional resilience, while the mid-career musicians reported distress, confusion, and anxiety about their identity as musicians. In the present follow-up study we aimed to examine the impact of the first year of the pandemic on the lives of 21 of the same musicians. We found that while all the mid-career participants remained committed to their performing careers, many late-career participants aged 54-59 had developed interests in non-performing music work, and the older late-career participants, aged 65 and over, feared that they might already, de facto, have retired. We discuss the findings with reference to the precarity of freelance orchestral musicians’ lives, lifespan models of musicians’ careers, self-determination theory and post-traumatic growth, and their implications for music colleges and musicians’ support organisations.